Effect of 2,4-D as a novel inducer of embryogenesis in microspores of Brassica napus L. - Samad Habibzadeh ARDEBILI; Mehran E. SHARIATPANAHI; Reza AMIRI; Mona EMAMIFAR; Mahnaz OROOJLOO; Ghorbanali NEMATZADEH; Seyed Ahmad Sadat NOORI; Erwin HEBERLE-BORS (Czech Journal of Genetics and Plant Breeding, 2011)
The effect of 2,4-dichlorophenoxyacetic acid (2,4-D) applied at high concentrations for a short time was investigated as a novel stress for induction of microspore embryogenesis for the first time. Brassica napus L. cvs. Topas and Hyola 420 were used as model plants for testing this hypothesis. Microspores were subjected to 2,4-D at 4 concentrations (15, 25, 35 and 45 mg/l) for 15-45 min while the classical heat shock was used as the control treatment. Among 2,4-D treatments in Topas, the highest yield of torpedo-stage embryos was achieved at 15 mg/l 2,4-D for 30 min while more normal plantlets were produced when 2,4-D (25 mg/l for 30 min) was applied to the microspores. In Hyola 420 the results showed a lower number of embryos and normal plantlets at all concentrations of 2,4-D. Although Hyola 420 was almost equally embryogenic as Topas after heat shock treatment, large differences between genotypes (concerning embryogenic response) occurred after 2,4-D treatment. However, the mean number of embryos and regenerants was higher in heat shock as compared to 2,4-D induced stress (one magnitude of order). According to the results obtained, 2,4-D can be introduced as a new stress for induction of embryogenesis in microspores similarly like in zygotic and somatic cells. This novel stress is very important for plant species whose microspores are extremely sensitive to classical stresses.